Hambatan Dalam Pengembangan Gastrodiplomasi Untuk Mencapai Brand Image Kuliner Indonesia di Era Pemerintahan Joko Widodo - kartini, eka (Universitas Bosowa, 2022)
In Joko Widodo's regime, several efforts have been made by the government in developing Indonesian gastrodiplomacy, namely product marketing and culinary festivals through collaboration with Wonderful Indonesia partners, Bekraf, Diaspora, Indonesian Chef Association and the food product industry. However, these efforts have not been able to achieve a brand image of Indonesian culinary on the international scene. The method that the researcher uses in this research is a qualitative method. The data collection technique used was Literature Study and conducted interviews with several resource persons who were experts in their fields. The author uses the concept of gastrodiplomacy. There are several factors that hinder the development of gastrodiplomacy in the era of Joko Widodo's administration, including product marketing that has not been maximized, festival plan that has not been strategic, certification constraints, use of media, and the application of culinary education that has not been maximized. In this case, the government does not yet have a strategic plan for sustainable and long-term gastrodiplomacy policies.